Gender in the Perspective of Islamic Shari'a and Constitution (Straightening the View of the Relationship between Women and Men) - Muhammad Sabir; Aris Aris (LPPM IAIN Parepare, 2021)
This research discussed about the relationship between men and women. In the existing reality, women are still marginalized since ancient times until now. This is due to the influence of understanding on religious texts and various other factors so that the differences in the relationship between the two can be seen in all aspects of life. The research method used is library research. In this study, it is argued that in the perspective of Islamic law, the relationship between the two is the same in terms of identity to the creator (worship of mahdah and gairu mahdah) as well as in the constitution that everyone has the same rights on politic, law, voting, and education. Everyone without exception has protection and right in the law.